What art is - Danto, Arthur Coleman (Yale University Press, 2013)
"What is it to be a work of art? Renowned author and critic Arthur C. Danto addresses this fundamental, complex question. Part philosophical monograph and part memoiristic meditation, What Art Is challenges the popular interpretation that art is an indefinable concept, instead bringing to light the properties that constitute universal meaning. Danto argues that despite varied approaches, a work of art is always defined by two essential criteria: meaning and embodiment, as well as one additional criterion contributed by the viewer: interpretation. Danto crafts his argument in an accessible manner that engages with both philosophy and art across genres and eras, beginning with Plato's definition of art in The Republic, and continuing through the progress of art as a series of discoveries, including such innovations as perspective, chiaroscuro, and physiognomy. Danto concludes with a fascinating discussion of Andy Warhol's famous shipping cartons, which are visually indistinguishable from the everyday objects they represent. Throughout, Danto considers the contributions of philosophers including Descartes, Kant, and Hegel, and artists from Michelangelo and Poussin to Duchamp and Warhol, in this far-reaching examination of the interconnectivity and universality of aesthetic production."--Publisher's website